Adequação de técnicas e ferramentas para a gestão estratégica em micros e pequenas empresas: uma proposta - Almeida, Simone de (2005)
The present work proposes a method to support it the micron and small companies, in the elaboration and formalization of its strategies, through the development of a management method that allows to give sustentation to the established strategies to reach the goals of the company. It was used as field of research and for the elaboration of the taxionomia, three situated companies in the state of the Paraná in the region of Ponta Grossa, of the area of pharmaceutical skillful formula manipulation, deliverering of gas and maintenance and resale of celulares devices. The particularities, limitations and objectives of the same ones are considered. This study it involved the application of the suitable method of the main tools of management, already validated in the scope of the company of great transport, to provide to the micron and small companies more efficient information in the decision taking guaranteeing bigger competitiveness. For the construction of the model, different aspects presented and developed in diverse boardings for evaluation of performance had been considered and others, decurrent of the relations discovered in the stage of the analysis of the companies where the model was applied. The studied model develops the method for analysis of performance of the business processes and its impact on the yield of the company. It objectives to supply information to legalize a Strategical Planning the Micron and Small Companies structuralizing it in the identification of performance pointers, critical factors in the attainment of the projected result for the company.